Stable Long-Term Culture of Human Distal Airway Stem Cells for Transplantation - Yueqing Zhou; Yujia Wang; Dandan Li; Ting Zhang; Yu Ma; Wei Zuo (Stem Cells International)
There is a population of p63+/Krt5+ distal airway stem cells (DASCs) quiescently located in the airway basal epithelium of mammals, responding to injury and airway epithelial regeneration. They hold the ability to differentiate into multiple pulmonary cell types and can repopulate the epithelium after damage. The current study aims at gaining further insights into the behavior and characteristics of the DASCs isolated from the patient lung and exploring their clinical translational potential. Human DASCs were brushed off through the bronchoscopic procedure and expanded under the pharmaceutical-grade condition. Their phenotype stability in long-term cell culture was analyzed, followed by safety evaluation and tumorigenic analysis using multiple animal models including rodents and nonhuman primate. The chimerism of the human-mouse lung model indicated that DASC pedigrees could give rise to multiple epithelial types, including type I alveolar cells as well as bronchiolar secretory cells, to regenerate the distal lung. Taken together, the results suggested that DASC transplantation could be a promising therapeutic approach for unmet needs in respiratory medicine including the COVID-19-related diseases.